Content management systems in libraries : (Scarecrow Press, 2008)
Content Management Systems in Libraries documents case studies related to two types of CMS implementations: those that manage content on library websites and those that manage digital content. This book brings together a number of case studies on current CMS implementations, using both open source and proprietary systems, and reflects on the current state and future of CMS in libraries.